Principal Component Analysis Of Pigeonpea {Cajanus Cajan (L.) Millispaugh} Germplasm (Applied Biological Research, 2020)
Ninety three genotypes of pigeonpea were evaluated in the Department of  Pulses, TNAU, Coimbatore (India) on the basis of principal component  analysis during kharif 2018-2019. The germplasms, including four checks, were subject to augmented completely randomized design (augmented  design I) for evaluation. Of the 13 principal components identified, the first  five principal components accounted for 75.21% of total variation among  the genotypes studied. The first principal component analysis explained  25.88% variation which gradually reduced to 18.16% in PC2, 12.63% in  PC3, 10.36% in PC4 and 8.17% in PC5. The cluster analysis based on 13 quantitative characters grouped all the genotypes into 5 main clusters. The  cluster I, II, III, IV and V had 1, 2, 5, 7 and 78 genotypes, respectively. The  study revealed that hybridization programme can be performed with elite  genotypes viz., ICP 12057, ICP 8819, ICP 11124, IC 525463 and IC 525413  from different clusters to develop high yielding pigeonpea varieties.
Keywords: Biometric traits; clusters; genetic diversity; pigeonpea; principal component analysis